Desarrollo de una herramienta software para determinar la ruta de acarreo de mineral más corta - Li Fernández, María H (2013)
In this research work, we have developed a software tool that allows determining the shortest mineral hauling road, in less time and at lower cost, in order to be employed by mining companies in Peru._x000D_ During development, it has been used data as distances and slopes of the sections that make up each mineral hauling road, information that has been provided by the staff that is working in a company of this kind._x000D_ After obtaining the data, we proceed to calculate the equivalent plane distance of each road by the Conversion Method of Hauling Roads to Equivalent Plane Distance in order to determine the shortest road._x000D_ Depending on the tonnage of mineral per carry, each company evaluates the number of roads in need for its fleet of trucks circulate normally, therefore, the software tool provides the possibility of compare two or more mineral hauling routes, displaying an increasingly sorted list based on the equivalent plane distance. With this functionality, the company decides how many roads from the list use._x000D_ According to tests, the software tool calculates, in a correct way, values of equivalent plane distance of each road and sorts the results in ascending effectively and efficiently. Therefore, it has been possible to develop a Software Tool to Determine the Shortest Mineral Hauling Road